Greenhouse Gasses Inventory on Textile Finishing Industry PT X - Efendy, Ryan Phillip; Dewi, Kania (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
The textile industry has the biggest impact on environmental pollution in the world, and is responsible for 10% of global carbon production. Most of the waste in the textile industry, is generated from the dyeing process and textile processing. PT X is a textile finishing industry, that focuses on finishing processes like dyeing and textile processing. In this research, GHG (greenhouse gasses) emission inventory was carried out to see how much GHG generated in the textile finishing industry. The inventory will focus on CO2, CH4, and N2O from generator, curing machine, operational vehicle, and electricity usage. The inventory methodology was based on IPCC 2006, that stated to determine GHG emission, an activity data and emission factor from that source is needed. This emission inventory results on the total emissions of 666.38 tonCO2eq or 258.629 kgCO2eq/tonproduct GHG emission from PT X in 2021. The GHG emission in PT X are dominated by CO2 gas. Which most of comes from electricity usage source. GHG emission produce by PT X are not high compared with similar industries, but can be improved further more with mitigation measures such as installing a solar panel, and constructed wetland.